Impersonals, passives, and impersonal pronouns: Lessons from Lithuanian. (18th November 2021) - Šereikaitė, Milena
Abstract: This study examines the properties of VoiceP and impersonal pronouns by contrasting two constructions in Lithuanian: the ‐ma / ‐ta impersonal and the canonical passive. I argue that, while these two constructions overlap morphologically, they are syntactically distinct. The ‐ma / ‐ta impersonal is related to the ‐no / ‐to construction in Polish and in Ukrainian. Although it patterns with the Ukrainian ‐no / ‐to passive in allowing an auxiliary, it behaves like an active VoiceP with a null projected initiator in a thematic‐subject position, a pattern found in the Polish ‐no / ‐to impersonal and other impersonals crosslinguistically. I show that the Lithuanian passive lacks a syntactically realized initiator and selects for a type of Voice without a specifier. I also analyze the properties of the impersonal pronoun of the ‐ma / ‐ta impersonal, demonstrating that it is a bare N that lacks inherently specified ɸ features (number, gender, and person) and has no case. This finding supports existing proposals that treat impersonal pronouns in different languages as defective.